PENGEMASAN PEMBELAJARAN TARI GUEL BERBASIS MEDIA INTERAKTIF KOMPUTER MENGGUNAKAN PROGRAM MACROMEDIA FLASH 8 UNTUK TINGKAT SMP - Mutiara, Yomanda Carissa (Gesture: Jurnal Seni Tari, 2022)
Abstract - This research aimed to describe the stages in packaging Guel dance learning based on interactive computer media using the Macromedia Flash 8 program for junior high school level.The theories used in this study are related to learning media (Susilana and Riyana 2016), and also from Syafdi Maizora related to Macromedia Flash 8 programs usage.This research designs are qualitative and quantitative. The population in this study was regional artists, traditional leaders and the Gayo communities in Central Aceh district, while the study sample was 2 dancers as dance performers and sources of data to collect data to fulfill Basic Competencies of Appreciation and Expression.Packaging was divided into 3 stages, first stage was collecting supporting materials according to material needs. After the materials were collected and had been summarized, the next stage was the process of working on Macromedia Flash 8. The final stage was validating the program in terms of language, text, layout, and the validity of the concept and then the media is ready to use. The stages in packaging Guel dance learning were achieved through collaboration in creating Macromedia Flash 8 animations. Findings obtained from the evaluation of validation tests from 2 material expert validators and 2 media expert validators were 95.01% and 77.27%. The end of the feasibility test of this assessment recapitulation was 86.14%, which showed that the packaging Guel dance learning based on interactive computer media for junior high school level is included in the very feasible category to use. Keywords: Packaging, Guel Dance, Interactive Computer Media, Macromedia  Flash 8 Abstrak - Penelitan ini merupakan penilitian yang bertujuan untuk mendeskripsikan tahapan-tahapan dalam pengemasan pembelajaran tari Guel berbasis media interaktif komputer menggunakan  program Macromedia Flash 8 untuk tingkat SMP. Teori yang digunakan dalam penelitian ini adalah tentang teori media (Susilana dan Riyana 2016), dan Syafdi Maizora tentang penggunaan program Macromedia Flash 8. Jenis penelitian ini adalah kualitatif dan kuantitatif. Populasidalam penelitian ini tertuju kepada seniman daerah, tokoh adat dan masyarakat Gayo kabupaten Aceh Tengah, sementara sampel penelitian adalah 2 orang penari yang bertujuan sebagai peraga tari dan nara sumber guna pengumpulan data untuk memenuhi Kompetensi Dasar Apresiasi dan Ekspresi. Pengemasan dibagi menjadi 3 tahapan, Mengumpulkan bahan pendukung sesuai dengan kebutuhan materi. Setelah bahan terkumpul dan materi telah dirangkum, selanjutnya proses pengerjaan Macromedia Flash 8. Evalusi program dari segi bahasa, teks, tata letak, dan kebenaran konsep dan kemudian siap digunakan. Tahapan-tahapan dalam pengemasan pembelajaran tari Guel dicapai melalui kerjasama dalam pembuatan animasi Macromedia Flash 8. Hasil yang didapat berdasarkan evaluasi uji validasi dari 2 orang validator ahli materi dan 2 orang validator ahli media masing-masing adalah 95.01% dan 77.27%. Akhir dari pada uji kelayakan dari rekapitulasi penilaian ini adalah 86.14% yaitu pengemasan pembelajaran tari Guel berbasis media interaktif komputer untuk tingkat SMP termasuk ke dalam kategori sangat layak untuk digunakan di lapangan. Kata Kunci :Pengemasan, Tari Guel, Media Interaktif komputer, Macromedia  Flash 8